Movement Disorders Emergencies - Rajan, Suraj; Kaas, Bonnie; Moukheiber, Emile (Seminars in Neurology, 2019)
Many acute and potentially life-threatening medical conditions have hyperkinetic or hypokinetic movement disorders as their hallmark. Here we review the clinical phenomenology, and diagnostic principles of neuroleptic malignant syndrome, malignant catatonia, serotonin syndrome, Parkinsonism hyperpyrexia, acute parkinsonism, acute chorea-ballism, drug-induced dystonia, and status dystonicus. In the absence of definitive lab tests and imaging, only a high index of clinical suspicion, awareness of at-risk populations, and variations in clinical presentation can help with diagnosis. We also discuss the principles of management and rationale behind treatment modalities in the light of more recent evidence.
Keywords: neuroleptic malignant syndrome; serotonin syndrome; acute dystonic reaction; oculogyric crisis; Parkinsonism hyperpyrexia; antipsychotics; tardive dyskinesia; acute Parkinsonism; drug-induced dystonia; malignant catatonia